Estrogen metabolites for the diagnosis of schistosomiasis associated urinary bladder cancer - Botelho, M.C. (2016)
In a recent issue of Cancer Letters Gouveia and colleagues [1] studied a series of 40 Angolan patients diagnosed with Urogenital Schistosomiasis (UGS). They reported that 45% of them presented UGS-associated Squamous Cell Carcinoma (SCC) and/or urothelial cell carcinoma [1]. In addition these authors performed Liquid Chromatography-Mass Spectrometry and this analysis revealed numerous estrogens like metabolites. These schistosome infection-associated metabolites included Catechol Estrogen Quinones (CEQ) and CEQ-DNA-adducts, two of which had been identified previously in S. haematobium [1-3]. They conclude suggesting that these metabolites can be expected to provide deeper insights into the carcinogenesis UGS-induced bladder cancer, and as biomarkers for diagnosis and/or prognosis of this neglected tropical disease-linked cancer. (...)